The Effect of Educational Board Games Training Programme on the Social Skill Development of the Fourth Graders - Bengü Türkoğlu (Elementary Education Online, 2023)
This research was conducted to explore the effect of Educational Board Games Training Programme (EBGTP) on the social skill development of the fourth graders. EBGTP is a training programme that is based on educational board games that aim to improve the social skills of the children. The pre-test/post-test model with control group was used for the research since it is a real experimental model. A total of 80 children (40 experimental subjects, 40 control subjects) were included in the research. A General Information Form and the Social Skill Evaluation Scale 7–12 (SSES 7–12) were used as data collection tool. EBGTP was formulated by the investigator, in a regular and controlled manner an hour a day, two days a week, for a period of 10 weeks, corresponding to a total of 20 hours. During the data analysis, dependent group t-tests were conducted for intra-group comparisons and independent group t-tests were used for inter-group comparisons. In conclusion, EBGTP which was provided to 40 fourth graders in primary school was detected to have a significantly positive effect on the social skill development of children.